Local cartilage trauma as a pathogenic factor in autoimmunity (one hypothesis based on patients with relapsing polychondritis triggered by cartilage trauma). (2012)
In the recent years, it has been of great interest to study the binding mechanism between the innate and adaptive immune responses as interrelated processes for the development of multiple autoimmune diseases. Infection has been a well-known trigger of autoimmunity and trauma has been related as well too. Cryptogenic antigens release, recognition of pathogenic structure, and metabolic changes generated by both stimuli begin an inflammatory process which in turn activates the immune system amplifying T and B cell responses. The development of relapsing polychondritis after trauma may have a direct association with these events and in turn probably trigger autoimmune phenomena.